Effect of the nanofilm-coated zirconia ceramic on resin cement bond strength - Viviane Maria Gonçalves de Figueiredo; Alecsandro de Moura Silva; Marcos Massi; Argemiro Soares da Silva Sobrinho; José Renato Cavalcanti de Queiroz; João Paulo Barros Machado; Renata Falchete do Prado; Lafayette Nogueira Junior (Tabriz University of Medical Sciences, 2022)
Background. New surface treatments have been proposed to expand the clinical indications of zirconia prostheses. This study aimed to evaluate the effect of silica and fluorine nanofilms on zirconia ceramic on the resin cement bond strength. Methods. Zirconia blocks and discs underwent different surface treatments: untreated zirconia (CON), sandblasted, silica-coated alumina particles (30 µm) (SC), silica nanofilm (SN), and fluorine nanofilm (FN). Nanofilm deposition was performed through plasma enhanced chemical vapor deposition (PECVD). Zirconia surfaces were characterized on disks by morphology (atomic force microscopy, AFM), chemical analysis (x-ray photoelectron spectroscopy, XPS), and contact angle analysis. A silane coupling agent was applied on each treated surface, and a cylinder of resin cement was built up. Half of the specimens in each group were submitted to 6000 thermal cycles (TC). Bond strength was analyzed using the shear test, and the fractographic analysis was performed with stereomicroscopy and SEM/EDS. Statistical analysis was performed through one-way ANOVA and Tukey test in the non-aged and aged specimens. Results. Nanofilms modified the zirconia surface, which became more hydrophilic and chemically reactive. Chemical bonding between Si-O was found in SN, and FN promoted a fluorination process on the ceramic surface, converting zirconia into zirconium oxyfluoride. Specimens of the SN (TC) group failed on pre-testing. FN (TC) bond strength (3.8 MPa) was lower than SC (TC) and CON (TC) after shearing. Adhesive failure predominated in the experimental groups. Silica nanofilm failure occurred after aging. Conclusion. Silica and fluorine nanofilms deposited by PECVD did not promote effective bonding between zirconia and resin cement.